Evaluation of primary stability of single implants placed in fresh extraction sockets: a clinical trial. Issue 2 (3rd March 2016) - De Angelis, Nicola; Sorrenti, Eugenio; Modena, Claudio; Benedicenti, Stefano
ABSTRACT: Dental implants have been used for the last 20 years. With the latest modern developments, however, minimally invasive protocols and immediate implants are currently used. The aim of this study was to evaluate the primary stability of a new implant design. Thirty immediate implants were placed and they all achieved successful osseointegration. Primary stability was reached with all the implants after the first apical threads. Within the limitations of the present study, the immediate implant approach seems to be a predictable treatment option, especially in conjunction with a specifically designed implant system.